CATALOGUE OF THE NOMINAL TAXA OF MESOAMERICAN PACHYCHILIDAE (MOLLUSCA: CAENOGASTROPODA) - Gomez-Berning, Maria; Köhler, Frank; Glaubrecht, Matthias (Zootaxa, 2012)
The caenogastropod family Pachychilidae Troschel, 1858 is a monophyletic group of freshwater snails that is distributedin the tropical regions of the world, where they exhibit high levels of endemism at the species and generic levels. Thereare many uncertainties regarding generic affiliation and species names in the Mesoamerican Pachychilidae owing to theirrelatively variable shells, the lack of distinctive anatomical features and the intricate taxonomic histories. In an attempt toconsolidate the knowledge of this taxon in the Neotropics, we provide here a catalogue of all available names of theMesoamerican pachychilid fauna, laying the foundation for future taxonomic revisions. Primary types were located for 56species-group taxa, and lectotypes for 22 nomina were designated. 102 nominal taxa of Mesoamerican pachychilids wereoriginally described. We consider that six of these taxa belong to other cerithioidean families. Two nomina are consideredto be unnecessary replacement names (Melania renovata Brot, 1862; Pachychilus tristrami Crosse & Fischer, 1892). Twotaxa are South American species that were incorrectly associated with Mesoamerican taxa (Pachychilus laevissimus sensuReeve, 1860; Melania laevissima var. decollata Brot, 1875). The exact type locality of Pachycheilus dalli Pilsbry, 1896and Melania mexicana were identified, and we accept Pachychilus hinkleyi (Marshall, 1920) as replacement name of the invalid Sphaeromelania hinkleyi Marshall, 1920.